PENGARUH SISTEM REWARD AND PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT. SULOTCO JAYA ABADI DI TANA TORAJA - Datu, Angelita Ratte; Roswiyanti (LPPM Universitas Muhammadiyah Bulukumba, 2025)
Employee performance plays a crucial role in determining organizationalsuccess. This study aims to examine the effect of reward and punishment on employeeperformance at PT. Sulotco Jaya Abadi, Tana Toraja. A quantitative method wasemployed using a saturated sampling technique with 50 respondents. Data werecollected through documentation, questionnaires, and interviews, and analyzed usingSPSS version 25 with validity and reliability tests, multiple linear regression, t-test,and F-test. The results showed that reward and punishment simultaneously have asignificant effect on employee performance (F value = 20.463; significance = 0.000 <0.05). Partially, reward has a significant effect (significance = 0.010; t value = 2.694 >t table = 2.011), and punishment also has a significant effect (significance = 0.009; tvalue = 2.731 > t table = 2.011).